Coping Strategies and Psychological Well-Being of Male and Female Prisoners - F.A. Sharipova (Психология и право)
The article presents the results of a study of coping strategies and psychological well-being among male and female prisoners. The study involved 109 people (53 men and 56 women), prisoners of the Execution Colony of Punishments in Tashkent, region Zangiata. In this study we have used complex of three methods: “The Strategic Approach to Coping Scale (SACS)” originally constructed by Stevan E. Hobfoll (Russian adaptation by N.E. Vodopyanova and E.S. Starchenkova), “The Scale of Subjective Well-Being” originally constructed by A. Perrudet-Badoux, G. Mendelsohn, J. Chiche (Russian adaptation by M.V. Sokolova), “Psychological Well-being scale” originally constructed by C. Ryff (Russian adaptation by T.D. Shevelenkov and P.P. Fesenko). Based on these results it is concluded that male prisoners in comparison with female prisoners experience tension and lack of life goals, are more focused on social coping strategies, such as Seeking Social Support and Social Joining. To identify the general and specific factors were also conducted factor analysis. Three general factors are “Environment and self management”, “Antisocial manipulation”, “Social activity”. The specific male factors are “Social coping”, “Destructive coping”. The specific female factors are “Autonomy”, “Emotional status”.